A porous polyurethane composite material and a preparation method thereof

The surfactant formed by the coordinated assembly of nanoparticles and aminolated polymer ligands solves the problems of oil-in-oil emulsion stability and mechanical properties of porous polyurethane materials, and achieves simple and efficient emulsion preparation and strength improvement of porous materials. in the field of biological tissue engineering.

CN116444849BActive Publication Date: 2024-12-20BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310412980.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2024-12-20
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

The preparation of existing oil-in-oil Pickering emulsions is difficult, and the traditional surfactant is used in large quantities and requires complex chemical modification steps, which limits the mechanical properties and pore size distribution control of porous polyurethane materials, especially in the field of biological tissue engineering. Application restricted.

Method used

The surfactant formed by the coordinated assembly of nanoparticles and aminolated polymer ligands is used to form an oil-in-oil high-inner phase Pickering emulsion through high-speed shearing, and a porous polyurethane composite material with uniform pore size and increased strength is obtained through continuous phase polymerization.

Benefits of technology

It realizes the development of simple and efficient emulsion stabilizer, avoids complex synthesis steps, reduces the dosage of traditional emulsifiers, avoids cavity problems caused by water side reactions, and improves the mechanical strength and pore size distribution uniformity of porous materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116444849B_ABST
    Figure CN116444849B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of porous materials and their preparation, and specifically relates to a porous polyurethane composite material and a preparation method thereof. In the present invention, nanoparticles, organic acids, polyols and isocyanates are added to a polar organic solvent to prepare a polar oil phase, and then a non-polar oil phase containing an amino polymer ligand is added to the polar oil phase. The nanoparticles and the amino polymer ligands are synergistically assembled to form a surfactant to successfully stabilize an oil-in-oil high internal phase Pickering emulsion, and the high internal phase emulsion is polymerized by heating to obtain a porous polyurethane composite material. The present invention avoids cumbersome synthesis and modification steps and a large amount of emulsifier addition, and the obtained polyurethane material is hydrophobic as a whole, has a small and uniformly distributed pore size, and does not have large-sized cavities; at the same time, the nanoparticles play a reinforcing role, so that the strength of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of porous materials and preparation thereof, and relates to a method for preparing a porous polyurethane composite material by using a surfactant-stabilized oil-in-oil high internal phase Pickering emulsion formed by the coordinated assembly of nanoparticles and polymer ligands and the high internal phase emulsion as a template. Background Art

[0002] Oil-in-oil (O / O) emulsions are mostly composed of immiscible polar phases and non-polar phases of organic solvents, breaking through the application limitations of aqueous emulsions in water-incompatible systems. Their development and growth are crucial to exploring the loading, separation, release and chemical reactions of water-sensitive substances. In existing reports on O / O emulsions, solid particles and block copolymers are often used to stabilize O / O emulsions. However, both types of emulsifiers require cumbersome chemical modification / synthesis steps, and the production process is relatively complicated. Emulsions stabilized by solid particles are also called Pickering emulsions. Compared with ordinary emulsions, they have the advantages of less emulsifier usage, high emulsion stability, and relatively low toxicity. Pickering emulsions can be stabilized by solid particles alone or by the coordinated assembly of particles and other ligands. The coordinated assembly strategy can avoid cumbersome synthesis or modification steps, and the emulsifier can be customized on demand by selecting particles and ligands. However, the current mainstream oil-in-oil Pickering emulsion emulsifier is a single modified nanoparticle, such as modified silica and modified graphene oxide, which is relatively difficult to prepare. Therefore, a simple O / O emulsion stabilizer is urgently needed to be developed.

[0003] Polyurethane porous materials, also known as polyurethane foam plastics, are the most widely used variety of polyurethane products. They have low density, high specific strength, and are odorless, highly thermally insulating, uniform in pores, resistant to aging, and resistant to organic solvent erosion. They are widely used in the automotive industry, construction materials, logistics packaging and other fields. Conventional foaming methods are difficult to control the pore size distribution of foams, and the pore size is relatively large, which seriously limits its development in the fields of biological tissue engineering. The high internal phase emulsion (HIPEs) template method is a simple and effective method for preparing porous materials. The pore size of the prepared porous materials is small and easier to control. However, when the water-containing high internal phase emulsion is used as a template, due to the inevitable side reaction between the isocyanate group and water, urea groups and carbon dioxide gas will be generated, resulting in large-sized cavities in the material, which will destroy the overall performance. If you want to solve the problem of large dosage of traditional surfactants while avoiding the adverse effects of water loss, and give porous polyurethane materials stronger mechanical properties, it is crucial to develop an oil-in-oil high internal phase Pickering emulsion template. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for stabilizing an O / O high internal phase emulsion by using a nanoparticle surfactant to replace a traditional surfactant without the need for complex synthetic modification steps; the second purpose is to provide a method for preparing a porous polyurethane material using an O / O high internal phase Pickering emulsion as a template. The present invention uses a surfactant formed by assembling nanoparticles and an amino polymer ligand to stabilize an O / O high internal phase Pickering emulsion, and then initiates continuous phase polymerization to remove excess components to obtain a porous polyurethane composite material with uniform pore size and improved strength.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a porous polyurethane composite material, comprising the following steps:

[0007] (1) fully dispersing or dissolving the nanoparticles, organic acid, isocyanate, and polyol in a polar organic solvent to prepare a polar oil phase mixture;

[0008] (2) adding the non-polar oil phase mixture containing the amino polymer ligand to the polar oil phase mixture of step (1), and high-speed shearing at more than 1000 r / min to obtain an oil-in-oil type high internal phase Pickering emulsion;

[0009] (3) The high internal phase Pickering emulsion obtained in step (2) is transferred to a convection oven and heated to react for 24 hours to obtain a solid crude product. The reaction temperature is 60° C. to 100° C., and then excess components are removed using acetone and n-hexane. After vacuum drying, a porous polyurethane composite material is obtained.

[0010] In the preparation method of the porous polyurethane composite material, the organic acid is one or more of acetic acid, caproic acid, citric acid, oxalic acid, succinic acid and trifluoroacetic acid, and the weight of the organic acid is 0.2-5% of the weight of the polar oil phase mixture.

[0011] The preparation method of the porous polyurethane composite material, the isocyanate includes one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and dimers and trimers of the above isocyanates, and the weight of the isocyanate is 5-30% of the weight of the polar oil phase mixture. The above isocyanate refers to one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and dicyclohexylmethane diisocyanate, and the isocyanate can be selected from isocyanate monomers or isocyanate monomer mixtures, isocyanate dimers or trimers, or mixtures of dimers and trimers, and can also be selected from monomers and dimers and trimers.

[0012] In the preparation method of the porous polyurethane composite material, the polyol comprises one or more of polyester polyol and polyether polyol, and the weight of the polyol is 1-10% of the weight of the polar oil phase mixture.

[0013] In the method for preparing the porous polyurethane composite material, the polar organic solvent is one or both of dimethyl sulfoxide and N,N-dimethylformamide.

[0014] The preparation method of the porous polyurethane composite material, the nanoparticles include one or more of cellulose nanocrystals, cellulose nanofibers, carboxyl silicon dioxide nanoparticles, carboxyl ferrosoferric oxide nanoparticles, nano-montmorillonite and graphene oxide, and the weight of the nanoparticles is 0.5% to 5% of the weight of the polar oil phase mixture.

[0015] The preparation method of the above-mentioned porous polyurethane composite material, the amino polymer ligand is one or more of amino cage polysilsesquioxane, amino polystyrene, single-terminal amino polydimethylsiloxane and double-terminal amino polydimethylsiloxane, and the weight of the amino polymer ligand is 0.5% to 5% of the weight of the non-polar oil phase mixture.

[0016] In the method for preparing the porous polyurethane composite material, the non-polar oil in step (2) is one or more combinations of silicone oil, n-hexane, octane, dodecane, petroleum ether and paraffin oil.

[0017] In the method for preparing the porous polyurethane composite material, the volume fraction of the Pickering emulsion internal phase is 75% to 90%.

[0018] A porous polyurethane composite material is a porous polyurethane composite material prepared by the preparation method of the porous polyurethane composite material.

[0019] The beneficial effects of the present invention are:

[0020] (1) The present invention develops a surfactant-stabilized oil-in-oil high internal phase Pickering emulsion formed by the coordinated assembly of nanoparticles and polymer ligands and a method for preparing a porous polyurethane composite material using the same. The surfactant is simple and efficient, avoids complex synthesis and modification steps, and the dosage is greatly reduced compared with traditional emulsifiers.

[0021] (2) Using oil-in-oil high internal phase Pickering emulsion as a template, hydrophilic and water-sensitive monomers were used to prepare hydrophobic polyurethane porous materials, avoiding the appearance of large-sized cavities caused by the side reaction of isocyanate and water, and obtaining porous materials with uniform pore size distribution and better integrity.

[0022] (3) Nanoparticles are often used as reinforcing and toughening materials because of their large specific surface area, highly activated surface active atoms, and strong interfacial interaction with polymers. The present invention uses a high internal phase emulsion template stabilized by nanoparticle surfactants to prepare a porous polyurethane composite material, which can improve the mechanical strength of the porous polyurethane material to a certain extent compared to traditional emulsifiers. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1-a This is a scanning electron microscope image of the porous polyurethane material prepared in Example 1;

[0024] Figure 1-b This is a scanning electron microscope image of the porous polyurethane material prepared in Example 2;

[0025] Figure 1-c This is a scanning electron microscope image of the porous polyurethane material prepared in Example 3;

[0026] Figure 1-d This is a scanning electron microscope image of the porous polyurethane material prepared in Comparative Example 1;

[0027] Figure 2-a Static water contact angle test diagram of the porous polyurethane material prepared in Example 1;

[0028] Figure 2-b Static water contact angle test diagram of the porous polyurethane material prepared in Example 2;

[0029] Figure 2-c Static water contact angle test diagram of the porous polyurethane material prepared in Example 3;

[0030] Figure 2-d Static water contact angle test diagram of the porous polyurethane material prepared in Comparative Example 1;

[0031] Figure 3 The pressure-strain curves of the polyurethane porous materials prepared in Example 3 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific examples. Obviously, the described examples are only some preferred embodiments of the present invention, and the present invention is not limited to these examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources.

[0033] Example 1

[0034] First, cellulose nanocrystals (CNC) are dispersed in DMSO and acetic acid is added to obtain a CNC dispersion containing acetic acid. Subsequently, polymerization monomers mannitol and hexamethylene diisocyanate trimer (polyHDI) are added to the dispersion, and the DMSO phase is obtained after full dissolution. The mass fraction of CNC in the DMSO phase is 1%, the mass fraction of acetic acid in the DMSO phase is 1%, the mass fraction of mannitol in the DMSO phase is 7%, and polyHDI: mannitol = 1:1 (molar ratio). In addition, amino cage polysilsesquioxane (POSS-NH2) is dissolved in dimethyl silicone oil to obtain a silicone oil phase, wherein the mass fraction of POSS-NH2 in the silicone oil phase is 1%. The silicone oil phase is added to the DMSO phase at a volume ratio of DMSO phase: silicone oil phase = 1:3, and a high-speed shearing is obtained to obtain an oil-in-oil type Pickering high internal phase emulsion with an internal phase volume fraction of 75%. The obtained high phase emulsion was transferred to a convection oven and reacted at 60°C for 24 hours to obtain a solid product. Then, acetone and n-hexane were used to remove excess components, and the porous polyurethane composite material was obtained by vacuum drying.

[0035] Example 2

[0036] The specific experimental steps were the same as those in Example 1, wherein polyHDI:mannitol=3:2 (molar ratio).

[0037] Example 3

[0038] The specific experimental steps were the same as those in Example 1, wherein polyHDI:mannitol=2:1 (molar ratio).

[0039] Comparative Example 1

[0040] Using polyethylene oxide propylene oxide block copolymer (F-127) as an emulsifier, mannitol, polyHDI and F-127 were first fully dissolved in DMSO to obtain a DMSO phase, wherein the mass fraction of mannitol in the DMSO phase was 7%, polyHDI: mannitol = 2:1 (molar ratio), and the mass fraction of F-127 in mannitol was 5%. The silicone oil phase was pure dimethyl silicone oil. The silicone oil phase was added to the DMSO phase at a volume ratio of DMSO phase: silicone oil phase = 1:3, and an oil-in-oil type Pickering high internal phase emulsion with an internal phase volume fraction of 75% was obtained by high-speed shearing. The obtained high internal phase emulsion was transferred to a convection oven, reacted at 60°C for 24 hours to obtain a solid product, and acetone and n-hexane were used to remove excess components, and a porous polyurethane composite material was obtained by vacuum drying.

[0041] Performance Testing

[0042] (1) Scanning electron microscope (SEM)

[0043] The morphology of the porous materials prepared in Examples 1-3 and Comparative Example 1 was analyzed using a S-4700 scanning electron microscope, with an accelerating voltage of 20 kV. Before the sample was tested, the surface was subjected to a gold spraying treatment. Figure 1-a to Figure 1-d ,in, Figure 1-a to Figure 1-c The scanning electron microscope images of the porous polyurethane composite materials of Examples 1-3 are respectively, Figure 1-d This is a scanning electron microscope image of the porous polyurethane composite material of Comparative Example 1. Figure 1-a to Figure 1-d It can be seen that the pore structure of the porous polyurethane composite materials prepared in Examples 1-3 is mostly closed pores, a small number of pores are interconnected, and the pore size distribution is relatively uniform, while the pore structure of the porous polyurethane composite material prepared in Comparative Example 1 is mostly through-pore structure, and the pore size distribution is uneven.

[0044] (2) Water contact angle test (WCA)

[0045] Multifunctional tension meter ( The water contact angle test was performed on the porous nanocomposites prepared in Examples 1-3 and Comparative Example 1 using the sessiledrop module of DSA30. The test results are shown in Figure 2-a to Figure 2-d , where 1-a to Figure 1-c are the water contact angles of the porous polyurethane composite materials of Examples 1-3, Figure 2-d It is the water contact angle of the porous polyurethane composite material of comparative example 1. As the -NCO / -OH (molar ratio) ratio increases, the water contact angle of the obtained porous material increases, and the hydrophobic property is improved.

[0046] (3) Mechanical properties test

[0047] The compression performance of Example 3 and Comparative Example 1 was characterized by a universal material testing machine. The test sample was a cylinder with a diameter of 10 mm and a height of 10 mm, and the compression strain was 70%. The test results are shown in Figure 3 . Comparative Example 1 shows a linear region at low strain, followed by a stress platform, and the yield limit is about 0.93MPa. Example 3 also shows a linear region at low strain, the Young's modulus is larger than that of Comparative Example 1, and the yield limit is about 4.98MPa. The test results show that the polyurethane porous material prepared by the surfactant-stabilized emulsion template assembled in collaboration with CNC and polymer ligands has higher mechanical strength than the polyurethane material prepared by the emulsion template stabilized by ordinary surfactants, indicating that CNC as a component of the surfactant also enhances the mechanical properties of the material.

[0048] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with the profession can make some changes or modify the technical content disclosed above to an equivalent embodiment of equivalent changes without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a porous polyurethane composite material, characterized in that: The steps include: (1) fully dispersing or dissolving nanoparticles, organic acid, isocyanate and polyol in a polar organic solvent to prepare a polar oil phase mixture; the nanoparticles include one or more of cellulose nanocrystals, cellulose nanofibers, carboxyl silicon dioxide nanoparticles, carboxyl ferric oxide nanoparticles, nano-montmorillonite and graphene oxide, and the weight of the nanoparticles is 0.5% to 5% of the weight of the polar oil phase mixture; (2) adding a non-polar oil phase mixture containing an amino polymer ligand to the polar oil phase mixture of step (1), and high-speed shearing at 1000 r / min or above to obtain an oil-in-oil type high internal phase Pickering emulsion; the amino polymer ligand is one or more of amino cage polysilsesquioxane, amino polystyrene, single-terminated amino polydimethylsiloxane and double-terminated amino polydimethylsiloxane, and the weight of the amino polymer ligand is 0.5% to 5% of the weight of the non-polar oil phase mixture; (3) The high internal phase Pickering emulsion obtained in step (2) is transferred to a convection oven and heated to react for 24 hours to obtain a solid crude product. The reaction temperature is 60°C to 100°C, and then the excess components are removed by acetone and n-hexane. After vacuum drying, a porous polyurethane composite material is obtained.

2. The method for preparing the porous polyurethane composite material according to claim 1, characterized in that: The organic acid comprises one or more of acetic acid, caproic acid, citric acid, oxalic acid, succinic acid and trifluoroacetic acid, and the weight of the organic acid is 0.2-5% of the weight of the polar oil phase mixture.

3. The method for preparing the porous polyurethane composite material according to claim 1, characterized in that: The isocyanate includes one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and dimers and trimers of the aforementioned isocyanates, and the weight of the isocyanate is 5-30% of the weight of the polar oil phase mixture.

4. The method for preparing the porous polyurethane composite material according to claim 1, characterized in that: The polyol comprises one or more of polyester polyol and polyether polyol, and the weight of the polyol is 1-10% of the weight of the polar oil phase mixture.

5. The method for preparing the porous polyurethane composite material according to claim 1, characterized in that: The polar organic solvent is one or both of dimethyl sulfoxide and N,N-dimethylformamide.

6. The method for preparing the porous polyurethane composite material according to claim 1, characterized in that: The non-polar oil in step (2) is one or more combinations of silicone oil, n-hexane, octane, dodecane, petroleum ether and paraffin oil.

7. The method for preparing a porous polyurethane composite material according to claim 1, characterized in that: The volume fraction of the internal phase of the Pickering emulsion is 75% to 90%.

8. A porous polyurethane composite material, characterized in that: The porous polyurethane composite material is a porous polyurethane composite material prepared by the method for preparing a porous polyurethane composite material according to any one of claims 1 to 7.

Citation Information

Cited By

  • High internal phase emulsion as well as preparation method and application thereof

    CN121695725A